2022
DOI: 10.14715/cmb/2022.68.3.19
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of BSA-coated Au Nanoparticles Contrast Agent and Its Application in PETCT Imaging

Abstract: Tumors are the biggest opponents in the history of human diseases, and they cannot be eliminated so far. The only way to treat tumors is to detect them early so that the survival rate can be improved by early treatment. For tumor detection, CT scan is the most commonly used, and PET/CT is an enhanced version of CT technology. Although PET/CT can produce relatively clear images of the human body, due to the complex structure of the human body, there are many ghosts and shadows, and the images cannot be accurate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…[40][41][42] Owing to the emission of low-energy photoelectrons and the interaction of Auger electrons, high-Z nanomaterials can absorb, scatter, and eradicate radiation energy. Moreover, when compared with other metal-based nanomaterials, Au-based nanomaterials are most widely used for this purpose, owing to the following advantages it offers: 1) a strong X-ray attenuation 1960 capability that makes it suitable for use in computer tomography (CT) imaging contrast agent and radiosensitizer [43][44][45] ; 2) as it can be easily surface-modified and embedded in structures such as liposomes and polymer particles, it is frequently used in different tumor treatment protocols; 3) as an inert metal, it exhibits good biocompatibility and low biotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42] Owing to the emission of low-energy photoelectrons and the interaction of Auger electrons, high-Z nanomaterials can absorb, scatter, and eradicate radiation energy. Moreover, when compared with other metal-based nanomaterials, Au-based nanomaterials are most widely used for this purpose, owing to the following advantages it offers: 1) a strong X-ray attenuation 1960 capability that makes it suitable for use in computer tomography (CT) imaging contrast agent and radiosensitizer [43][44][45] ; 2) as it can be easily surface-modified and embedded in structures such as liposomes and polymer particles, it is frequently used in different tumor treatment protocols; 3) as an inert metal, it exhibits good biocompatibility and low biotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Au NPs possess good surface modifiability and can be further used for reducing NP toxicity and improving biocompatibility in vivo through coating with specific protective molecules. Bovine serum albumin (BSA) is a common surface modifier for metal NPs 9 , and BSA-coated Au NPs (BSA-Au) have been widely used for tumor monitoring and treatment 10,11 . For instance, Murawala et al 12 prepared BSA-Au NPs loaded with methotrexate (MTX) and demonstrated that BSA-Au-MTX had a more significant inhibitory effect on breast cancer cells than an equivalent dose of free MTX.…”
Section: Introductionmentioning
confidence: 99%